The predictability of implicit causes: testing frequency and topicality explanations. Issue 10 (26th November 2021) - Guan, Shuang; Arnold, Jennifer E.
ABSTRACT: In discourses involving implicit causality, the implicit cause of the event is referentially predictable, that is, it is likely to be rementioned. However, it is unclear how referential predictability is calculated. We test two possible explanations: (1) The frequency account suggests that people learn that implicit causes are predictable through experience with the most frequent patterns of reference in natural language, and (2) the topicality account asks whether implicit causes tend to play topical roles in the discourse, which itself may lead to the perception of discourse accessibility. With two text analyses we show that implicit causes are frequently rementioned, but only if we consider a narrow set of discourse circumstances, which would require comprehenders to track contingent frequencies. We found no evidence for the topicality account: in two experiments, implicit causality affected predictability but not topicality, and in a corpus of natural speech, implicit causes tended to not occupy topical positions.